Gender differences in acute myocardial infarction—A nationwide German real‐life analysis from 2014 to 2017. Issue 7 (1st June 2021) - Kuehnemund, Leonie; Koeppe, Jeanette; Feld, Jannik; Wiederhold, Achim; Illner, Julia; Makowski, Lena; Gerß, Joachim; Reinecke, Holger; Freisinger, Eva
Abstract: Background: Female sex was reported to be associated with an unfavorable outcome in acute myocardial infarction (AMI). In this nationwide analysis we assessed sex differences in acute outcomes of AMI and recent trends in patient healthcare. Methods: We analyzed 875 735 German cases hospitalized with a main diagnosis of ST‐ (STEMI) and non ST‐elevation myocardial infarction (NSTEMI) between January 01 2014 and December 31 2017 regarding morbidity, in‐hospital mortality and treatments. A multivariable logistic regression model was designed to evaluate the use of interventions and their impact on in‐hospital mortality. Results: STEMI cases decreased from 72 894 in 2014 to 68 213 in 2017, with 70% assignable to men. Female sex was associated with older age (74 vs. 62 years), and higher prevalence of cardiovascular risk factors such as chronic kidney disease (19.2% vs. 12.5%), hypertension (69.0% vs. 65.0%) and left ventricular heart failure (36.0% vs. 32.1%). In NSTEMI, female sex was also associated with older age (78 vs. 71 years), and higher prevalence of cardiovascular risk factors such as chronic kidney disease (29.7% vs. 23.9%), hypertension (77.4% vs. 74.5%) and left ventricular heart failure (40.5% vs. 36.4%). Overall, 74.3% of female and 81.3% of male STEMI cases received percutaneous coronary intervention (PCI, p < 0.001). In NSTEMI, PCI was performed in 40.8% of female and 52.0% of male cases (p < 0.001). In‐hospital mortality was notably increased in female patients with STEMI (15.0% vs. 9.6%; p < 0.001; OR 1.07; 95% CI 1.03–1.10) and NSTEMI (8.3% vs. 6.3%; p < 0.001; OR 0.91; 95% CI 0.89–0.93) compared to males. Conclusions: Our nationwide real‐world data document that in‐patient STEMI cases continue to decrease in women and men. The observed higher in‐hospital mortality in women was largely attributed to a more unfavorable risk and age distribution rather than to female‐intrinsic factors. Women with AMI continue to be less likely to receive revascularization therapies.